A CONTRIBUTION TO THE GEOLOGICAL STRUCTURE OF CHIOS ISLAND, EASTERN AEGEAN SEA - Tselepidis, V.; Rondoyanni, Th. (Bulletin of the Geological Society of Greece, 2010)
Τhe island of Chios, in the eastern Aegean Sea, is of great geological interest due to the outcrops of the oldest Paleozoic rocks of the Hellenides. Three main geological units of Paleozoic and Mesozoic age dominate, that have a tectonic relationship: the Autochthonous unit is overthrusted by the Parautochthonous unit, which in turn is overthrusted by the Allochthonous unit. In this work, new geological and tectonic data concerning the Autochthonous unit and especially its part of the Paleozoic - Mesozoic transition are presented and evaluated. Due to the rare outcrops of this transition and the lack of sufficient palaeontological data, there are various and contradictory opinions concerning its normal or discordant character. Based on our field data and lithostratigraphic correlations, we can draw the following main results: Considering the Autochthonous unit, the transition of the Paleozoic formations to the Mesozoic ones is characterized by an angular unconformity as well as by a basal conglomerate. In some places there is a tectonic contact between them, this of a thrust fault. The Lower Triassic formations of the Parautochthonous unit belong to the Autochthonous unit, since they present similar palaeogeographic conditions. Moreover, the presence of the “Hallstatt” limestones in the Autochthonous unit can be explained by their local deposition in lenticular form.